The First Zagreb Index and the Narumi-Katayama Index of the Non-Commuting Graph on the Group U_{6n} - Khairatun Hisan; Ibrahim Gambo; I Gede Adhitya Wisnu Wardhana (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2025)
This paper introduces a novel approach to computing the First Zagreb and Narumi–Katayama indices for non-commuting graphs associated with specific algebraic groups, specifically focusing on the group U_{6n}. The Narumi–Katayama index, first introduced by Narumi and Katayama in 1984, is a degree-based topological index widely used in the study of various graph properties, including its applications in theoretical chemistry. Non-commuting graphs, where two elements are adjacent if and only if they do not commute, have become an intriguing object of study in recent years. To the best of our knowledge, this is the first study to derive closed-form expressions for the First Zagreb and Narumi–Katayama indices on the non-commuting graph of the group U_{6n}. Building on previous research on the detour index and eccentric connectivity in the graph Γ(U_{6n}), this work makes new contributions by deriving generalized formulas that apply to a broader class of non-commutative groups. Unlike previous studies that focused on commuting or coprime graphs, this research specifically addresses the structure and index computation of non-commuting graphs in a group-theoretic context. The findings offer new theoretical insights into algebraic graph theory by linking degree-based indices with the internal structure of non-abelian groups. These results are expected to expand the understanding of the topological properties of non-commuting graphs and to provide valuable connections to chemical applications.Keywords: Non-commuting graph; First Zagreb Index; Narumi–Katayama Index; graph topology; group structure. AbstrakArtikel ini memperkenalkan pendekatan baru untuk menghitung indeks First Zagreb dan Narumi–Katayama pada graf non-commuting yang terkait dengan grup aljabar tertentu, khususnya berfokus pada grup U_{6n}. Indeks Narumi–Katayama, yang pertama kali diperkenalkan oleh Narumi dan Katayama pada tahun 1984, adalah indeks topologis berbasis derajat yang banyak digunakan dalam studi berbagai properti graf, termasuk penerapannya dalam kimia teoretis. Graf non-commuting, di mana dua elemen saling berhubungan jika dan hanya jika mereka tidak komutatif, telah menjadi objek studi yang menarik dalam beberapa tahun terakhir. Sejauh yang kami ketahui, ini adalah studi pertama yang menghasilkan ekspresi bentuk tertutup untuk indeks First Zagreb dan Narumi–Katayama pada graf non-commuting dari grup U_{6n}. Berdasarkan penelitian sebelumnya tentang indeks detour dan konektivitas eksentrik pada graf Γ(U_{6n}), karya ini memberikan kontribusi baru dengan menghasilkan rumus umum yang dapat diterapkan pada kelas grup non-komutatif yang lebih luas. Berbeda dengan studi sebelumnya yang berfokus pada graf commuting atau coprime, penelitian ini secara khusus membahas struktur dan perhitungan indeks pada graf non-commuting dalam konteks teori grup. Hasil penelitian ini memberikan wawasan teoretis baru dalam teori graf aljabar dengan menghubungkan indeks berbasis derajat dengan struktur internal grup non-abelian. Diharapkan, temuan ini akan memperluas pemahaman tentang properti topologis graf non-commuting dan memberikan koneksi yang berharga untuk penerapan kimia.Kata Kunci: Graf non-commuting; Indeks Zagreb Pertama; Indeks Narumi–Katayama; Topologi graf; Struktur grup. 2020MSC: 05C25, 05C09, 20D60, 05C75.